Analisis Lagu Bernuansa Jawa pada Perayaan Ekaristi di Gereja Stasi Kabar Gembira Kotabumi - Maria Angelika Intan Ristyaloka; Erizal Barnawi; Bian Pamungkas (Grenek: Jurnal Seni Musik, 2025)
One of the most important parts that cannot be separated from the Eucharistic Celebration is the songs accompanying each procession. The songs used in the Eucharistic Celebration have various types. One popular form is the Inculturation song form. This study will discuss the use of the Javanese Inculturation song form used in the Eucharistic Celebration at the Kabar Gembira Catholic Church in Kotabumi using the Qualitative-Descriptive Research model. This study aims to analyze and describe the songs "Aku Mengasih Tuhan", "Bapa Kami Gaya Jawa", and "Ndherek Dewi Mariyah". Data was collected through observation, interviews, and documentation. The data that had been collected was then analyzed using the theory of "Musical Form Science" by Karl-Edmund Prier SJ and the theory of "Javanese Inculturation Music Form" by Ardhana. This study found the Canon musical form in the three songs analyzed. This study also found that the Javanese nuances contained in the songs analyzed can be seen based on the composition or tuning, as well as the language used in the presentation of the song.